Diode laser treatment of posterior retinopathy of prematurity. Issue 12 (1st December 2000) - Axer-Siegel, Ruth; Snir, Moshe; Cotlear, Dan; Maayan, Ayala; Frilling, Ronit; Rosenbaltt, Irit; Weinberger, Dov; Kremer, Israel; Sirota, Lea
Abstract : AIMS: To study the efficacy of infrared diode laser for the treatment of posterior retinopathy of prematurity (ROP). METHODS: 48 eyes of 25 premature babies (mean birth weight 779 (SD 127.7) g; mean gestational age 25.5 (SD 1.47) weeks) with threshold ROP in zone I and posterior zone II were treated by the indirect infrared (810 nm) diode laser. Confluent burns were applied to the avascular retina. In 18 eyes, an additional row of laser burns was added posterior to the ridge. RESULTS: Favourable anatomical results were noted in 41 eyes (85.4%). ROP stage 5 developed in two eyes, ROP stage 4A developed in four eyes, and ROP stage 4B in one eye. Three of the eyes with stage 4A eyes were successfully buckled; the fourth was not operated on and remained demarcated by laser scars. No complications were noted. CONCLUSION: In this series, the diode laser was found to be a safe and effective treatment for posterior ROP.